Association of triple positivity with prognostic parameters and overall survival in a population-based study of 6,122 HER2-positive breast cancer patients: analysis of real-world clinical practice based on a research database - Kolářová, Iveta; Vaňásek, Jaroslav; Doležel, Martin; Štuk, Jan; Hlávka, Aleš; Dušek, Ladislav; Melichar, Bohuslav; Büchler, Tomáš; Ryška, Aleš; Prausová, Jana; Petráková, Katarína; Tesařová, Petra; et al. (My University, 2020)
Triple-positive breast cancer (TPBC), i.e. HER2-positive (HER2+) and hormone receptors-positive breast cancer, is a specific subgroup of breast cancers. TPBC biology is characterized by strong mutual interactions between signaling pathways stimulated by estrogens and HER2 amplification. The present study aims to carry out a population-based analysis of treatment outcomes in a cohort of hormone receptor (HR) positive and negative breast cancer patients who were treated with anti-HER2 therapy in the Czech Republic. The BREAST research database was used as the data source for this retrospective analysis. The database covers approximately 95% of breast cancer patients treated with targeted therapies in the Czech Republic. The analysis included 6,122 HER2-positive patients. The patients were divided into two groups, based on estrogen receptor (ER) or progesterone receptor (PR) positivity: hormone receptor negative (HR-) patients had both ER- and PR-negative tumors (n=2,518), unlike positive (HR+) patients (n=3,604). HR+ patients were more often diagnosed premenopausal at the time of diagnosis, presented more often at stage I or II and their tumors were less commonly poorly differentiated. The overall survival (OS) was significantly higher in subgroups of HR+ patients according to treatment setting. When evaluated by stages, significantly higher OS was observed in HR+ patients diagnosed at stages II, III, and IV and regardless of tumor grade.
‎Asociace trojité pozitivity s prognostickými parametry a celkové přežití v populační studii 6 122 pacientů s her2 pozitivním karcinomem prsu: analýza reálné klinické praxe na základě výzkumné databáze‎
Keywords: breast cancer; triple positive; HER2-positive; hormone receptors; trastuzumab; overall survival; rakovina prsu; trojnásobně pozitivní; HER2-pozitivní; hormonální receptory; trastuzumab; celkové přežití